PRACTICAL ASPECTS OF THE MECHANISM FOR MANAGING THE PERFORMANCE AND DEVELOPMENT OF ACTIVITIES OF NATIONAL ECONOMIC ENTITIES BASED ON DIGITALIZATION (INNOVATIVE ECONOMY, 2025)
Kuprina N.M. PRACTICAL ASPECTS OF THE MECHANISM FOR MANAGING THE PERFORMANCE AND DEVELOPMENT OF ACTIVITIES OF NATIONAL ECONOMIC ENTITIES BASED ON DIGITALIZATIONPurpose. The aim of the article is to substantiate the feasibility of using modern digital tools in the process of budgeting the future activities of a national economic entity in order to increase the efficiency of the management mechanism and the functioning of its personnel.Methodology of the research. The following research methods were used to achieve the set goal, in particular: to build the structure and logic of the article - the method of structural and logical analysis; to substantiate the use of the budgeting process and individual digital tools (Beyond Budgeting, Zero-Based Budgeting), for the functionality and characteristics of the UBC Analytics budgeting system on the IBM Planning Analytics platform – the method of analytical and comparative analysis, deduction, synthesis; for a visual presentation of the research results and characteristics of the structural components of the proposed digital tool – the UBC Analytics budgeting system on the IBM Planning Analytics platform – tabular and structuring method.Findings. It is substantiated that the use of such a tool as budgeting of the future activities of such an entity significantly increases the efficiency of management personnel and allows you to form a profitable business, ensure financial stability, the effectiveness of its future activities and build a development strategy.It is proposed for use in the budgeting process of such a digital tool by business entities in Ukraine as the UBC Analytics budgeting system on the IBM Planning Analytics platform. Its functionality and main characteristics are shown.Originality. The approach to using the UBC Analytics budgeting system on the IBM Planning Analytics platform in the mechanism for managing the activities of national economy entities was further developed, as a modern digital tool for planning the future activities of the entity, in order to increase the efficiency of the work of both management personnel and the entity of the national economy as a whole and build a strategy for its development.Practical value. The substantiated proposals based on the results of the study can be used in practical and managerial activities by state and local government bodies, auditing and consulting firms, business entities in order to ensure the efficiency of functioning, competitiveness, the formation of a profitable business, ensuring financial stability, the effectiveness of future activities and to build strategies for the development of entities of the national economy and the efficiency of their personnel, as well as by higher education institutions in educational activities for the training of specialists in economic specialties.Key words: management, mechanism, personnel, digital tools, formation, performance, development, budgeting process, strategy, national economy, entities.
Keywords: management; mechanism; personnel; digital tools; formation; performance; development; budgeting process; strategy; national economy; entities